Quarterlife Crisis in Young Adults: Challenges, Impacts, and Adaptation Processes - Wijaya, Zahwa Citra; Mantovani, Adinda Najwa; Kencana, Khaila Putri; Sepsita, Vera (Jurnal Psikologi Terapan, 2024)
Quarterlife crisis is a phenomenon commonly experienced by individuals in the transition from adolescence to adulthood, characterized by uncertainty in career, social relationships, and life goals. This study aims to analyze the factors influencing quarterlife crisis among young adults and its impact on psychological well-being. The research employs a quantitative approach with a survey method. The study sample consists of 200 respondents aged 18-30 years, selected using purposive sampling technique. Data were collected through an online questionnaire that includes a quarterlife crisis scale and a psychological well-being scale based on Ryff's model. The results indicate that most respondents experience a moderate to high level of quarter life crisis, particularly those in the early stages of their careers. Additionally, a significant negative relationship was found between quarter life crisis and psychological well-being, specifically in terms of self-acceptance and life purpose. These findings suggest that quarterlife crisis can lower psychological well-being but may also serve as an opportunity for personal growth if managed properly. The implications of this study highlight the importance of psychological and social support in helping individuals navigate quarter life crisis to enhance their psychological well-being. Future research is recommended to expand the sample scope and explore more effective intervention strategies for managing quarter life crisis.